Antologia Grega: apêndice de Planudes (livro XVI) - Jesus, Carlos A. Martins de (2017)
The Planudean, copied in the fourteenth-century autograph Marcianus gr. 481, was between the sixteenth and the eighteenth centuries the single known garland of Greek epigram, having had, therefore, a huge influence in modern poetry and culture in general. As a didactic text it was for Renaissance students of Greek and Latin, it was frequently their first contact with Greek literature. Poets and other writers made a large use of it. Erasmus is an example, he who copies and comments in his Adagia about 50 components, alongside Alciato’s Emblemmata, first published in 1492, where a much larger number of epigrams are illustrated, translated into Latin and commented. This volume offers in translation the epigrams transmitted by Planudes that are absent from the Palatinus, nowadays published as Book XVI of the Greek Antholoy. The larger part of them (356 out of 392) comes from chapter IV of the Marcianus, a collection of ecphrastic poems. Among them are the components dedicated to the charioteers of Constantinople (numbers 335-386), which archaeology proved to have been actually inscribed.